Pengembangan Sistem Informasi Asesmen Lembaga Sertifikasi Profesi Berbasis Web (Studi Kasus: SMK Negeri 4 Malang) - Arif Rahmadani Vinanda; Satrio Agung Wicaksono; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
SMK Negeri 4 Malang is one of the Institutions that gets a license as an organizer of professional certification for vocational students from National Professional Certification Agency (BNSP). In the professional certification proceses there are documents that must be filled in by the assessor kesimpuand students totaling more than 50 (fifty) pages for one student. This causes problems, filling process time, documents storage, and the use of excessive paper. In this research uses the Waterfall System Development Life Cycle (SDLC) without deployment process. For data collection methods using interview and observation methods on physical assessment documents in Rekayasa Perangkat Lunak study. From the results of interviews and observations, the software requirements are obtained for both actors (student and assessor), and then illustrated on several diagram of a unified modeling language before the implementation process using the PHP programming language and using the CodeIgniter framework. For the first testing process using the black-box method with an error guessing technique to get error possibility that will occur in the system. The results obtained are all possible errors can be handled properly indicated by all tests get valid results. For the second test, the user acceptance test method is used to see the acceptance of the system by the user using the questionnaire. The results obtained were all respondents gave "yes" answers to each question given. From these results an acceptance decision process for decision making related to acceptance shows that all functionalities or in terms of the usefulness of the system can be fully accepted by users, both students and assessors.